2018
DOI: 10.3390/nano9010016
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Charge Transfer Characteristics in Hierarchical Cu2S QDs @ ZnO Nanoneedles with p–n Heterojunctions: Towards Highly Efficient and Recyclable Photocatalysts

Abstract: Equipped with staggered gap p-n heterojunctions, a new paradigm of photocatalysts based on hierarchically structured nano-match-shaped heterojunctions (NMSHs) Cu2S quantum dots (QDs)@ZnO nanoneedles (NNs) are successfully developed via engineering the successive ionic layer adsorption and reaction (SILAR). Under UV and visible light illumination, the photocatalytic characteristics of Cu2S@ZnO heterojunctions with different loading amounts of Cu2S QDs are evaluated by the corresponding photocatalytic degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 118 publications
(118 reference statements)
4
7
0
Order By: Relevance
“…Figure 1 plots the network of keywords for the last eight years developed using Scopus database. e study indicates strong network relationship between photocatalysis, titanium dioxide, and nitrogen oxides which has also been found in literature review [16,17]. Recently, titanium dioxide nanoparticles, zinc oxide, and oxide minerals are used for manufacturing of concrete blocks.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Figure 1 plots the network of keywords for the last eight years developed using Scopus database. e study indicates strong network relationship between photocatalysis, titanium dioxide, and nitrogen oxides which has also been found in literature review [16,17]. Recently, titanium dioxide nanoparticles, zinc oxide, and oxide minerals are used for manufacturing of concrete blocks.…”
Section: Introductionsupporting
confidence: 57%
“…On the other hand, applications of photocatalysis have already been studied vastly in oxidation of pollutants in different environmental media, such as air, water, and soil [14,15]. Among the various oxidation agents, such as TiO 2 , ZnO, Ag 3 PO 4 , CuO, AgI, and Cu 2 S, TiO 2based photocatalysis was reported to be most advantageous because of its high efficiency, easier mobilization on different substrates, lower operational cost, and no damage to environment and living beings [16,17]. erefore, in recent years, scientific community is also working towards exploring the applicability of photocatalysis in reduction of urban-air pollution [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, in one study, the diffusion of K + ions from poly(heptazine imide) (PHIK) to a metal–organic framework (MOF) made PHIK more negatively charged and MOF more positively charged, which provided the strongest interaction between PHIK and MOF and resulted in superior photocatalytic activity through rhodamine B degradation [18]. It has also been shown that the formation of heterojunctions could increase photocatalytic properties, such as Cu 2 S/ZnO, Cu 2 O/TiO 2 , and CuInS 2 /TiO 2 [19,20,21], and that the presence of Na 2 S hole scavengers increased the photoreduction of CO 2 to form (HCOO − ) on ZnS [22]. Finally, due to the different Fermi levels between heavy metals and LDHs, heavy metals deposited on the surface of LDHs could act as electron traps to prevent electron-hole recombination [5,9,10], which would improve the photocatalytic performance of LDHs.…”
Section: Introductionmentioning
confidence: 99%
“…Sunlight-driven semiconductor-based heterogeneous photocatalysts have been extensively investigated due to their straightforward operation, environmental friendliness and high efficiency 13 . Thus, different semiconductors have been explored to improve their cost-efficiency, long-term stability and efficiency 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different semiconductors have been explored to improve their cost-efficiency, long-term stability and efficiency 46 . Among these, ZnO stands out due to its excellent characteristics, e.g., a direct wide band gap (Eg = 3.37 eV), good availability, cost effectiveness, low-toxicity, unique acoustic and optoelectronic properties, chemical stability and nanoscale tunability 712 . Nevertheless, the wide bandgap energy of ZnO allows the generation of excitons only upon UV light irradiation, which is less than 5% of the solar spectrum, hence limiting its performance as a solar photocatalyst.…”
Section: Introductionmentioning
confidence: 99%